The interaction between fishbone modes and shear Alfvén waves in tokamak plasmas. (31st March 2016) - He, Hongda; Liu, Yueqiang; Dong, J.Q.; Hao, G.Z.; Wu, Tingting; He, Zhixiong; Zhao, K.
Abstract: The resonant interaction between the energetic particle triggered fishbone mode and the shear Alfvén waves is computationally investigated and firmly demonstrated based on a tokamak plasma equilibrium, using the self-consistent MHD-kinetic hybrid code MARS-K (Liu et al 2008 Phys. Plasmas 15 112503 ). This type of continuum resonance, occurring critically due to the mode's toroidal rotation in the plasma frame, significantly modifies the eigenmode structure of the fishbone instability, by introducing two large peaks of the perturbed parallel current density near but offside the q   =  1 rational surface ( q is the safety factor). The self-consistently computed radial plasma displacement substantially differs from that being assumed in the conventional fishbone theory.